Biomolecular Chemistry in Liquid Phase Separated Compartments - Nakashima, Karina K.; Vibhute, Mahesh A.; Spruijt, Evan (Frontiers in Molecular Biosciences, 2019)
Biochemical processes inside the cell take place in a complex environment that is highly crowded, heterogeneous and replete with interfaces. The recently recognized importance of biomolecular condensates, many of which are formed by liquid-liquid phase separation (LLPS) and behave like liquid droplets, in cellular organization has added new elements of complexity to our understanding of chemistry in the cell. These droplet organelles can be reproduced and studied in vitro by using coacervates and have some remarkable features, including regulated assembly, differential partitioning of macromolecules, permeability to small molecules and a uniquely crowded environment. Here, we review the main principles of biochemical organization in model membraneless compartments. We focus on some promising in vitro coacervate model systems that aptly mimic part of the compartmentalized cellular environment. We address the physicochemical characteristics of these liquid phase separated compartments, and their impact on biomolecular chemistry and assembly. These model systems enable a systematic investigation of the role of spatiotemporal organization of biomolecules in controlling biochemical processes in the cell, and they provide crucial insights for the development of functional artificial organelles and cells.